The Relationship Between Sensation Seeking, Conformity, and Decision-Making Among Early Adult Female Vaporizer Users in Bogor City - Fadilah, Farhan; Aminah Alfalathi, Siti; Mayra, Zara (Lafadz Jaya Publisher, 2024)
A vaporizer is a type of device designed to convert nicotine into vapor without direct combustion. The decision to use this device is influenced by several factors, including sensation seeking and conformity. This study aims to (1) examine the relationship between sensation seeking, conformity, and decision-making, (2) explore the relationship between sensation seeking and decision-making, and (3) investigate the relationship between conformity and decision-making among early adult female vaporizer users in Bogor City. The study utilized purposive incidental sampling, with a sample of 66 female respondents aged 20–25 years residing in Bogor City. The research instruments included the Sensation Seeking Scale (r=0.718), Conformity Scale (r=0.740), and Decision-Making Scale (r=0.728). Data were analyzed using multiple linear regression and partial correlation analysis.